Canine and feline cytology : (Saunders/Elsevier, 2016)
Comprehensive coverage of all body systems and body fluids and the pathological changes associated with various infectious agents ― emphasizes areas in which the application of cytology has the greatest diagnostic value. Exceptional-quality, full-color photomicrographs show both normal and abnormal tissue and also include detailed legends. Discussions of clinical, differential, and cytological diagnosis accompany the illustrations of lesions and conditions in each chapter.